2022
DOI: 10.1146/annurev-animal-013120-043949
|View full text |Cite
|
Sign up to set email alerts
|

Chagas Disease Ecology in the United States: Recent Advances in Understanding Trypanosoma cruzi Transmission Among Triatomines, Wildlife, and Domestic Animals and a Quantitative Synthesis of Vector–Host Interactions

Abstract: Chagas disease, a neglected tropical disease present in the Americas, is caused by the parasite Trypanosoma cruzi and is transmitted by triatomine kissing bug vectors. Hundreds of vertebrate host species are involved in the ecology of Chagas disease. The sylvatic nature of most triatomines found in the United States accounts for high levels of animal infections but few reports of human infections. This review focuses on triatomine distributions and animal infections in the southern United States. A quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 134 publications
0
25
0
1
Order By: Relevance
“…In the southern US, the species in our study are typically considered sylvatic and are predominantly maintained by wildlife species. A recent quantitative synthesis from 14 published bloodmeal analysis studies of triatomines found in the US showed at least 44 host taxa/host groups represented among 449 insects, emphasizing their opportunistic and indiscriminate feeding behaviors 58 .…”
Section: Discussionmentioning
confidence: 99%
“…In the southern US, the species in our study are typically considered sylvatic and are predominantly maintained by wildlife species. A recent quantitative synthesis from 14 published bloodmeal analysis studies of triatomines found in the US showed at least 44 host taxa/host groups represented among 449 insects, emphasizing their opportunistic and indiscriminate feeding behaviors 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Chagas disease, also known as American trypanosomiasis, is a life-threatening disease caused by the protozoan parasite Trypanosoma cruzi. (T. cruzi) [67]. An estimated 6-7 million people worldwide are infected with T. cruzi, mostly in Latin America, the parasite that causes Chagas disease [68].…”
Section: Trypanosoma Cruzi Infection-induced Cardiomyopathymentioning
confidence: 99%
“…Trypanosoma cruzi transmission involves complex interactions between the parasite, multiple host species, and sylvatic vector populations [4,5]. As generalist vectors, triatomines feed on a broad range of domestic and wild mammals and other vertebrate species, each with varying roles in maintaining T. cruzi transmission cycles [5,6,7,8,9,10]. In domestic cycles of T. cruzi transmission, triatomines colonize human habitations and feed primarily on humans and domestic animals, while in the sylvatic cycle of transmission, triatomines live in nests or burrows, feeding on diverse wildlife species.…”
Section: Introductionmentioning
confidence: 99%